Parâmetros genéticos e tendências genéticas para características reprodutivas e de crescimento testicular em bovinos guzerá - Grupioni, Natalia Vinhal [UNESP]; Guidolin, Diego Gomes Freire; Venturini, Guilherme Costa [UNESP]; Lôbo, Raysildo Barbosa; Munari, Danisio Prado [UNESP] (My University, 2015)
This study aimed to estimate genetic parameters and genetic trends for reproductive traits and testicular growth in Guzerá cattle. Variance components were estimated through two-trait analyses using the restricted maximum likelihood method. To age at first calving (AFC), first calving interval (FC1), gestation period (GP), and scrotal circumference at 365 and 450 days (SC365 and SC450, respectively) were included the random residual and additive genetic effects and the fixed effects of contemporary group. The covariates cows age at calving and AFC were included in the model for SC365 and SC450 (linear and quadratic effects) and for FC1 (linear effect), respectively. For GP, The random maternal genetic effects were also considered. Heritability estimates ranged from 0.08 ± 0.05 (FC1) to 0.48 ± 0.11 (GP). Genetic trends were significant (P <0.05) for all traits with the exception of the maternal genetic effect of GP. The SC365, SC450 and GP traits, could be used as selection criteria for presenting additive genetic variability sufficient to respond to the selec-tion process. The genetic correlation between AFC and scrotal circumferences (SC365 and SC450) indicates that selection for scrotal circumference in these ages, reduce the AFC of the females.
Genetic parameters and genetic trends for testicular growth and reproductive traits in guzerá cattle
Keywords: Beef cattle; Genetic correlation; Genetic Variability; Scrotal circumference